Teaching the art of poetry : the moves - Wormser, Baron (Lawrence Erlbaum Assoc., 2000)
Concise and accessible, this guide to teaching the art of poetry from Shakespeare to contemporary poets enables anyone to learn about how poets approach their art. Teachers can use this book to explore any facet or era of poetry. Any reader can use it as an entryway into the art of poetry. Teaching the Art of Poetry shows poetry as a multi-faceted artistic process rather than a mystery on a pedestal. It demystifies the art of poetry by providing specific historical, social, and aesthetic contexts for each element of the art. It is a nuts-and-bolts approach that encourages teachers and students.